2018
DOI: 10.3390/atmos9110449
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Air Pollutants from Rice Residue Open Burning in Thailand, 2018

Abstract: Crop residue burning negatively impacts both the environment and human health, whether in the aspect of air pollution, regional and global climate change, or transboundary air pollution. Accordingly, this study aims to assess the level of air pollutant emissions caused by the rice residue open burning activities in 2018, by analyzing the remote sensing information and country specific data. This research also aims to analyze the trend of particulate matter 10 microns or less in diameter (PM10) concentration ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…According to [8], assessing the effects of open rice straw burning on air quality is difficult because these fires typically occur infrequently, for short periods of time, and in small rice paddy plots spread across a large region [8]. The study in Thailand was conducted by [29] and found that PM 2.5 concentrations ranged between 2-166 µg/m 3 over a 24 h period (daily standard 50 µg/m 3 ) and 9-36 µg/m 3 over an annual average, bringing the national average to 22 µg/m 3 (average standard 25 µg/m 3 ). Furthermore, the number of days when PM 2.5 concentrations exceeded the daily standard in Chiang Mai, a province in Thailand's northern region where many biomass open burning activities can be found during the summer, was reduced from 57 to 29 g/m 3 in 2016 compared to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…According to [8], assessing the effects of open rice straw burning on air quality is difficult because these fires typically occur infrequently, for short periods of time, and in small rice paddy plots spread across a large region [8]. The study in Thailand was conducted by [29] and found that PM 2.5 concentrations ranged between 2-166 µg/m 3 over a 24 h period (daily standard 50 µg/m 3 ) and 9-36 µg/m 3 over an annual average, bringing the national average to 22 µg/m 3 (average standard 25 µg/m 3 ). Furthermore, the number of days when PM 2.5 concentrations exceeded the daily standard in Chiang Mai, a province in Thailand's northern region where many biomass open burning activities can be found during the summer, was reduced from 57 to 29 g/m 3 in 2016 compared to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…According to a report issued by the Rice Department, around 18-29 million tons of residual rice straw was managed by burning it as paddy stubble on the field [148]. This has become a serious issue, causing air pollution due to the emission of gas and small dust particles [149].…”
Section: Rice Residuesmentioning
confidence: 99%
“…In order to tackle trade-offs from a scenario where an immense amount of biomass would flow into the bioenergy sector, the strategy requires an adequate method of biomass management, particularly in the case of Thailand. Even though agricultural residues have been deployed in several applications, the leftover agricultural residues generated in Thailand are presently not being exploited to their maximum potential [12,149]. Currently, around 50% of rice residues are managed in rice paddies through field burning or left unutilized in the fields [166].…”
Section: Palm Residuesmentioning
confidence: 99%
“…Jika musim kemarau sebagian jerami dimanfaatkan sebagai pakan ternak dan media penanaman jamur. Pembakaran jerami padi memberikan kontribusi peningkatan emisi gas rumah kaca seperti karbon dioksida (CO2), karbon monoksida (CO), karbon yang terbakar (dengan jumlah jejak metana), nitrogen oksida (NOx), dan jumlah jejak sulfur dioksida (SO2), bersama dengan lainnya partikulat (PM), (Andini, Bonnet, Rousset, & Hasanudin, 2018;Gadde, Bonnet, Menke, & Garivait, 2009;Junpen, Pansuk, Kamnoet, Cheewaphongphan, & Garivait, 2018;Lim, Manan, Wan Alwi, & Hashim, 2012). Diperkirakan tahun 2030 peningkatan emisi gas rumah kaca dari aktifitas pembakaran biomassa di Indonesia mengalami peningkatan 29% (Andini et al, 2018).…”
Section: Persepsi Tentang Pemanfaatan Jerami Padiunclassified